Midbrain stroke syndrome: Weber’s syndrome in two male HIV-positive patients with cerebral toxoplasmosis - Wong Armas, Jorge Luis (2023)
This report describes the case of two male HIV-positive patients who were not receiving treatment and whose diagnosis was confirmed by serology testing. Both patients developed midbrain stroke syndrome and the structural injury, whichwas caused by a central nervous system infection due to cerebral toxoplasmosis, was verified by brain magnetic resonance imaging. This condition was confirmed by cerebrospinal fluid serology testing.Weber’s syndrome is a very rare type of midbrain stroke syndrome with little information available on its symptoms and evolution. It was first described by Sir Herman David Weber in 1863 and is characterized by ipsilateral injury of the third cranial nerve fascicle with contralateral hemiparesis due to injury of the corticospinal and corticobulbar tracts of the cerebral peduncle. Its causes range from ischemic or hemorrhagic processes, which damage the third cranial nerve fascicle and cerebral peduncle, to brain tumors, aneurysms, extradural hematomas and infectious diseases that behave like spreading processes.The assessed patients showed clinical signs and symptoms such as ptosis; vertical double vision; difficulty standing up; hemiparesis; hyporeflexia; decreased superficial and deep sensation; poor balance and coordination; third cranial nervepalsy; slurred speech; intermittent disorientation in time, place and person; and facial asymmetry. Oral trimethoprim-